Hadith #2275 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Mhmwd bin Khalid محمود بن خالد; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
My people married me to a Roman slave-girl of theirs. I had intercourse with her, and she gave birth to a black (male) child like me. I named it Abdullah. I again had intercourse with her, and she gave birth to a black (male) child like me. I named it Ubaydullah. Then a Roman slave of my people, called Yuhannah, incited her, and spoke to her in his own unintelligible language. She gave birth to a son like a chameleon (red). I asked her: What is this? She replied: This belongs to Yuhannah. We the
Grade: Da'if

Hadith #2426 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdur-Razzaq عبد الرزاق بن همام; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
He said: Messenger of Allah, tell me about keeping fast on Monday and Thursday. He said: On it I was born, and on it the Qur’an was first revealed to me.
Grade: Sahih

Hadith #2481 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Mua'dh bin Hisham bin Aby معاذ بن هشام بن أبي عبد الله; Qatada قتادة; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
‘Amir said “A man came to ‘Abd Allaah bin ‘Amr while the people were with him. He sat with him and said “Tell me anything that you heard from the Apostle of Allaah(ﷺ)”. He said “I hears the Apostle of Allaah(ﷺ) say “A Muslim is he from whose tongue and hand the Muslims remain safe and an emigrant is he who abandons what Allaah has prohibited.””
Grade: Sahih

Hadith #2486 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Laith bin Sa'd الليث بن سعد; Ali bin 'Ayyash علي بن عياش; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي (Sunan Abi Dawud)
A man said: Messenger of Allah, allow tourism for me. The Prophet (ﷺ) said: The tourism of my people is striving in the path of Allah, the Exalted.
Grade: Hasan

Hadith #2488 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Isma'il bin Zakaria bin Mrh إسماعيل بن زكريا بن مرة; Matruf bin Tarayf al-Harithi مطرف بن طريف; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة (Sunan Abi Dawud)
A woman called Umm Khallad came to the Prophet (ﷺ) while she was veiled. She was searching for her son who had been killed (in the battle) Some of the Companions of the Prophet (ﷺ) said to her: You have come here asking for your son while veiling your face? She said: If I am afflicted with the loss of my son, I shall not suffer the loss of my modesty. The Messenger of Allah (ﷺ) said: You will get the reward of two martyrs for your son. She asked: Why is that so, Messenger of Allah? He repl
Grade: Da'if

Hadith #2496 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abdullah bin Yazid bin Zayd; Abu 'Abdur Rahman al-Habli عبد الله بن يزيد أبو عبد الرحمن الحبلي; Hameed bin Han'i Abu حميد بن هانئ أبو هانئ; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري (Sunan Abi Dawud)
Buraidah reported the Apostle of Allaah(ﷺ) as saying “Respect to be shown by those who stay at home to the women of those who are engaged in jihad is t be like that shown to their mothers. If any man among those who stay at home is entrusted with the oversight of one’s family who is engaged in jihad and betrays him, he will be setup for him on the Day of Resurrection and he (the mujahid) will be told “This (man) was entrusted with the oversight of your family, so take what you want from
Grade: Sahih

Hadith #2518 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; al-'Ala' bin 'Abdullah bin Rafa'i العلاء بن عبد الله بن رافع; Muslim bin Hatm مسلم بن حاتم (Sunan Abi Dawud)
‘Amr said “I heard from Abu Wa’il a tradition which surprised me, he then narrated the tradition to the same effect (as mentioned before).
Grade: Sahih

Hadith #2525 - Sunan Abi Dawud - Abdul Malik bin Shu'aib bin al-Laith عبد الملك بن شعيب بن الليث بن سعد; Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Laith bin Sa'd الليث بن سعد; Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي (Sunan Abi Dawud)
AbuAyyub heard the Messenger of Allah (ﷺ) say: Capitals will be conquered at your hands, and you will have to raise companies in large armies. A man will be unwilling to join a company, so he will escape from his people and go round the tribes offering himself to them, saying: Whose place may I take in such and such expedition? Whose place may I take in such and such expedition? Beware: That man is a hireling to the last drop of his blood.
Grade: Da'if

Hadith #2527 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Sa'ib bin Malik السائب بن مالك; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) announced an expedition, and I was a very old man and I had no servant. I, therefore, sought a hireling who would serve instead of me, and I would give him his portion. So I found a man. When the time of departure arrived, he came to me and said: I do not know what would be the portions, and how much would be my portion. So offer something (as wages) to me, whether there would be any portion or not. I offered three dinars (as his wages) for him. When some booty arriv
Grade: Sahih

Hadith #2528 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Sa'ib bin Farroukh, Abu al-Abbas السائب بن فروخ أبو العباس الشاعر; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A man came to the Messenger of Allah (ﷺ) and said: I came to you to take the oath of allegiance to you on emigration, and I left my parents weeping. He (the Prophet) said: Return to them and make them laugh as you made them weep.
Grade: Sahih

Hadith #2711 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Abdullah bin Shwdhb عبد الله بن شوذب الخراساني أبو عبد; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري (Sunan Abi Dawud)
Abu Hurairah said “We went out along with the Apostle of Allaah(ﷺ) in the year of Khaibar. We did not get gold or silver in the booty of war except clothes, equipment and property. The Apostle of Allaah(ﷺ) sent (a detachment) towards Wadi Al Qura. The Apostle of Allaah(ﷺ) was presented a black slave called Mid’am. And while they were in Wadi Al Qura and Mid’am was unsaddling a Camel belonging to the Apostle of Allaah(ﷺ) he was struck by a random arrow which killed him. The people s
Grade: Sahih

Hadith #2746 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu 'Abdur Rahman al-Habli عبد الله بن يزيد أبو عبد الرحمن الحبلي; Ahmed bin Salah al-Masri أحمد بن صالح المصري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to give to some of the detachments he sent out (something extra) for themselves in particular apart from the division made to the whole army. The fifth is necessary in all that.
Grade: Sahih

Hadith #2788 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Yazid bin Zayd; Ayyash bin 'Abbas al-Qanabi عياش بن عباس القتباني; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Isa bin Hilal عيسى بن هلال; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي (Sunan Abi Dawud)
We were staying with the Messenger of Allah (ﷺ) at Arafat; he said: O people, every family must offer a sacrifice and an atirah. Do you know what the atirah is? It is what you call the Rajab sacrifice. Abu Dawud said: ‘Atirah has been abrogated, and this tradition is an abrogated one.
Grade: Hasan

Hadith #2884 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Rafa'i al-Tnwkhy عبد الرحمن بن رافع التنوخي; Abdur Rahman bin Ziyad عبد الرحمن بن زياد بن أنعم; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر (Sunan Abi Dawud)
That his father died and left a debt of thirty wasqs of a Jew on him. Jabir asked him to defer, but he refused. Jabir then spoke to the Messenger of Allah (ﷺ) asking him to mediate to him on his behalf. The Messenger of Allah (ﷺ) came to the Jew and spoke to him about taking fruit-dates in lieu of the debt that was on him. But he refused. The Messenger of Allah (ﷺ) asked him to defer (the debt) to him, but he refused. He then narrated the rest of the tradition.
Grade: Sahih

Hadith #2910 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
I said: Messenger of Allah, where will you stay tomorrow ? This (happened) during his Hajj. He replied: Has ‘Aqil left any house for us ? He then said: We shall stay at the valley of Banu Kinarah where the Quraish took an oath on unbelief. This refers to al-Muhassab. The reason is that Banu Kinarah made an alliance with the Quraish against Banu Hashim that they would have no marital connections with them, nor will have commercial transactions with them, not will give them any refuge. Al-Zuhri
Grade: Sahih

Hadith #3087 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Ibn Ishaq محمد بن إسحاق بن يسار‎; Isma'il bin Umayya bin 'Amr إسماعيل بن أمية بن عمرو; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
Al-Miqdad went to Baqi’ al-Khabkhabah for a certain need. He found a mouse taking out a dinar from a hole. It then continued to take out dinars one by one until it took out seventeen dinars. It then took out a red purse containing a dinar. There were thus eighteen dinars. He took them to the Prophet (ﷺ), informed him and said to him: Take its sadaqah. The Prophet (ﷺ) asked him: Did you extend your hand toward the hole? He replied: No. The Messenger of Allah (ﷺ) then said: May Allah bless
Grade: Da'if

Hadith #3106 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu 'Abdur Rahman al-Habli عبد الله بن يزيد أبو عبد الرحمن الحبلي; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone visits a sick whose time (of death) has not come, and says with him seven times: I ask Allah, the Mighty, the Lord of the mighty Throne, to cure you, Allah will cure him from that disease.
Grade: Sahih

Hadith #3122 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abu 'Abdur Rahman al-Habli عبد الله بن يزيد أبو عبد الرحمن الحبلي; Rabi'ya bin Syf bin Mat' ربيعة بن سيف بن ماتع; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
When Zaid b. Harithah, Ja’far and ‘Abd Allah b. Rawahah were killed, the Messenger of Allah (ﷺ) sat down in the mosque and grief was visible in his face. Then he (the narrator) mentioned the rest of the tradition.
Grade: Sahih

Hadith #3356 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abu Sufyan ibn Harb; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Hammad bin Salama حماد بن سلمة; Ibn Ishaq محمد بن إسحاق بن يسار‎; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The Prophet (ﷺ) forbade selling animals for animals when payment was to be made at a later date.
Grade: Sahih

Hadith #3455 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Laith bin Sa'd الليث بن سعد; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
“Or one of them tells the other: “Exercise the right.”
Grade: Sahih

Hadith #3503 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Ayoub al-Sakhtiyani أيوب السختياني; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan Abi Dawud)
Hakim asked (the Prophet): Messenger of Allah, a man comes to me and wants me to sell him something which is not in my possession. Should I buy it for him from the market? He replied: Do not sell what you do not possess.
Grade: Sahih

Hadith #3539 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Usamah ibn Zayd (Sunan Abi Dawud)
The Prophet (ﷺ) said: It is not lawful for a man to make a donation or give a gift and then take it back, except a father regarding what he gives his child. One who gives a gift and then takes it back is like a dog which eats and vomits when it is full, then returns to its vomit.
Grade: Sahih

Hadith #3546 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
On his father’s authority, said that his grandfather reported the Messenger of Allah (ﷺ) as saying: It is not permissible for a woman to present a gift from the property which she has in her possession when her husband owns her chastity.
Grade: Hasan Sahih

Hadith #3579 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب (Sunan Abi Dawud)
“We will never employ or we shall not employ (the narrator is doubtful) in our work one who wants it.”
Grade: Sahih

Hadith #3645 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Walid bin 'Abdullah الوليد بن عبد الله بن أبي مغيث; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Ubaidullah bin al-Akhns عبيد الله بن الأخنس النخعي أبو مالك; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Yusuf bin Mahk يوسف بن ماهك الفارسي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) ordered me (to learn the writing of the Jews), so I learnt for him the writing of the Jews. He said: I swear by Allah, I do not trust Jews in respect of writing for me. So I learnt it, and only a fortnight passed before I mastered it. I would write for him when he wrote (to them), and read to him when something was written to him.
Grade: Hasan Sahih

Hadith #3662 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Mu'adh ibn Jabal; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) said: relate traditions from the children of Isra’il; there is no harm.
Grade: Sahih

Hadith #3684 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ibn Ishaq محمد بن إسحاق بن يسار‎; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
I asked the prophet (ﷺ) about wine made from honey. He said: That is bit. I said: And the one made from barley and millet ? He said :That is mizr. He then said: Tell your people that every intoxicant is prohibited.
Grade: Sahih

Hadith #3699 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Amr bin al-Aswad al-Ansi عمرو بن الأسود العنسي; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Ziyad bin Fyad al-Khza'y زياد بن فياض الخزاعي (Sunan Abi Dawud)
When the Messenger of Allah(ﷺ) forbade the use of(wine) vessels, Ansar said: They are inevitable for us. Thereupon he said: If so, then no
Grade: Sahih

Hadith #3791 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Muhammad bin Khalid bin محمد بن خالد; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Yahya bin Khlf al-Bahly يحيى بن خلف الباهلي أبو سلمة البصري (Sunan Abi Dawud)
I was an adolescent boy. I hunted a hare and roasted it. Abu Talha sent its hunch through me to the Prophet (ﷺ), so I brought it to him and he accepted it.
Grade: Sahih

Hadith #3868 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Yazid bin Zayd; Abdur Rahman bin Rafa'i al-Tnwkhy عبد الرحمن بن رافع التنوخي; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was asked about a charm for one who is possessed (nashrah). He replied: It pertains to the work of the devil.
Grade: Sahih

Hadith #4010 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdur Rahman bin Ziyad عبد الرحمن بن زياد بن أنعم; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
AbulMalih said: Some women of Syria came to Aisha. She asked them: From whom are you? They replied: From the people of Syria. She said: Perhaps you belong to the place where women enter hot baths (for washing ). The said: Yes. She said: I heard the Messenger of Allah (ﷺ) say: If a woman puts off her clothes in a place other than her house, she tears the veil between her and Allah, the Exalted. Abu Dawud said: This is the tradition narrated by Jarir, and it is more perfect. Jarir did not mentio
Grade: Sahih

Hadith #4067 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Muhammad bin 'Uthman al-Tnwkhy محمد بن عثمان التنوخي أبو الجماهر; Shrhbyl bin Muslim bin Hamd شرحبيل بن مسلم بن حامد الخولاني الشامي (Sunan Abi Dawud)
The word mudarrajah mentioned in the previous tradition means a colour which is neither crimson nor pink.
Grade: Da'if

Hadith #4068 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Mujahid bin Jabir مجاهد بن جبر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) saw me. The version of AbuAli al-Lula’ has: I think I wore a garment dyed with a reddish yellow colour. He asked: What is this? So I went and burnt it. The Prophet (ﷺ) said: What have you done with your garment? I replied: I burnt it. He said: Why did you not give it to one of your women to wear? Abu Dawud said: Thawr transmitted it from Khalid and said: “Pink (muwarrad)” while Tawus said: “Reddish yellow colour (mu’asfar)”.
Grade: Da'if

Hadith #4247 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Zayd bin Wahb al-Jhny زيد بن وهب الجهني (Sunan Abi Dawud)
He said: If you do not find a caliph in those days, then flee away until you die, even of you die holding on (to a stump of a tree). I asked: What will come next ? He replied: If a man wants the mare to bring forth a foal, it will not deliver in till the Last Hour comes.
Grade: Hasan

Hadith #4264 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Laith bin Sa'd الليث بن سعد; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
The Prophet (ﷺ) said: There will be civil strife (fitnah) which will render people deaf, dumb and blind regarding what is right. Those who contemplate it will be drawn by it, and giving rein to the tongue during it will be like smiting with the sword.
Grade: Da'if

Hadith #4307 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu Umama bin Sahl; Musa bin Jbyr al-Madni Mwla موسى بن جبير المدني; Zuhayr bin Muhammad al-Tamimi زهير بن محمد التميمي (Sunan Abi Dawud)
The Prophet (ﷺ) said: The people will establish cities, Anas, and one of them will be called al-Basrah or al-Busayrah. If you should pass by it or enter it, avoid its salt-marshes, its Kall, its market, and the gate of its commanders, and keep to its environs, for the earth will swallow some people up, pelting rain will fall and earthquakes will take place in it, and there will be people who will spend the night in it and become apes and swine in the morning.
Grade: Sahih

Hadith #4340 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Muslimah bin Qa'nab al-Harithi مسلمة بن قعنب الحارثي البصري (Sunan Abi Dawud)
I head the Messenger of Allah (ﷺ) say: If any one you sees something objectionable, he should change it with his hand if he can change it with his hand. (The narrator Hammad broke the rest of the tradition which was completed by Ibn al-‘Ala’.) But if he cannot (do so), he should do it with his tongue, and if he cannot (do so with) his tongue he should do it in his heart, that being the weakest form of faith.
Grade: Sahih

Hadith #4341 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hilal bin Khbab هلال بن خباب; Ikrama عكرمة; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Abi Dawud)
I asked AbuTha’labah al-Khushani: What is your opinion about the verse “Care for yourselves”. He said: I swear by Allah, I asked the one who was well informed about it; I asked the Messenger of Allah (ﷺ) about it. He said: No, enjoin one another to do what is good and forbid one another to do what is evil. But when you see niggardliness being obeyed, passion being followed, worldly interests being preferred, everyone being charmed with his opinion, then care for yourself, and leave alone
Grade: Hasan

Hadith #4374 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Ibn Jurayj ابن جريج; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
A Makhzumi woman used to borrow goods and deny having received them, so the prophet (ﷺ) gave orders that her hand should be cut off. The narrator than transmitted the rest of the tradition like that of al-laith, saying : So the prophet (ﷺ) had her hand cut off. Abu dawud said: Ibn Wahb transmitted this tradition from Yunus on the authority of al-Zuhri, and in this version he said al-Laith has said: A woman committed theft during the lifetime of the Prophet (ﷺ) on the occasion of the Conque
Grade: Sahih

Hadith #4388 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Laith bin Sa'd الليث بن سعد; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
Muhammad ibn Yahya ibn Hibban said: A slave stole a plant of a palm-tree from the orchard of a man and planted it in the orchard of his master. The owner of the plant went out in search of the plant and he found it. He solicited help against the slave from Marwan ibn al-Hakam who was the Governor of Medina at that time. Marwan confined the slave and intended to cut off his hand. The slave’s master went to Rafi’ ibn Khadij and asked him about it. He told him that he had heard the Messenger of
Grade: Sahih

Hadith #4545 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Qasim bin Rabi'ya bin Jwshn القاسم بن ربيعة بن جوشن; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Sulaiman bin Harb سليمان بن حرب; Uqba bin Aws (Sunan Abi Dawud)
The Prophet (ﷺ) said: The blood-wit for accidental killing should be twenty she-camels which had entered their fourth year, twenty she-camels which had entered their fifth year, twenty she-camels which had entered their second year, twenty she-camels which had entered their third year, and twenty male camels which had entered their second year. It does not beyond Ibn Mas’ud.
Grade: Da'if

Hadith #4564 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Husain bin Dhakwan al-Mua'lam الحسين بن ذكوان المعلم المكتب; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Khalid bin al-Harith bin 'Ubaid خالد بن الحارث بن عبيد; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو (Sunan Abi Dawud)
I found in my notebook from Shaiban and I did not hear from him ; Abu Bakr, a reliable friend of ours, said: Shaiban – Muhammad b. Rashid – Sulaiman b. Musad – ‘Amr b. Suh’aib, On his father’s authority, said that his grandfather said: The Messenger of Allah (ﷺ) would fix the blood-money for accidental killing at the rate of four hundred dinars or their equivalent in silver for townsmen, and he would fix it according to the price of camels. So when they were dear, he increased the
Grade: Hasan

Hadith #4586 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Qasim bin Rabi'ya bin Jwshn القاسم بن ربيعة بن جوشن; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Sulaiman bin Harb سليمان بن حرب; Uqba bin Aws (Sunan Abi Dawud)
On his father’s authority, said that his grandfather reported the Messenger of Allah (ﷺ) said: Anyone who practises medicine when he is not known as a practitioner will be held responsible. Abu Dawud said: This has been transmitted by al-Walid alone. We do not know whether it is sound or not.
Grade: Hasan

Hadith #4686 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Marrah al-Kharfi عبد الله بن مرة الهمداني الخارفي; Abdullah bin Numayr عبد الله بن نمير; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Masrouq bin al-Ajda' مسروق بن الأجدع; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
Do not turn unbelievers after me ; one of you may strike the neck of the other.
Grade: Sahih

Hadith #4740 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Bashr bin Shghaf بشر بن شغاف; Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Tarkhan al-Taymi سليمان بن طرخان التيمي (Sunan Abi Dawud)
People will come forth from Hell by Muhammad’s intercession, will enter paradise and be named Jahannamis.
Grade: Sahih

Hadith #4769 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Search for the man with crippled hand. He then mentioned the rest of the tradition. This version has: They took him out from beneath the slain in the dust. Abu al-wadi said: As if I am looking at an Abyssinian with a shirt on him. He had one of his hands like the nipple of the female breast, having hair on it like the hair on the tail of the jerboa.
Grade: Sahih

Hadith #4843 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Amr bin Shu'aib bin Muhammad عمرو بن شعيب بن محمد السهمي; Shu'aib bin Muhammad bin 'Abdullah شعيب بن محمد بن عبد الله بن عمرو; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Usamah bin Zayd al-Lythy أسامة بن زيد الليثي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Glorifying Allah involves showing honour to a grey-haired Muslim and to one who can expound the Qur’an, but not to one who acts extravagantly regarding it, or turns away from it, and showing honour to a just ruler.
Grade: Hasan Sahih

Hadith #4855 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Sa'id bin Abi Hilal سعيد بن أبي هلال الليثي; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: People who get up from an assembly in which they did not remember Allah will be just as if they had got up from an ass’s corpse, and it will be a cause of grief to them.
Grade: Sahih

Hadith #5063 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Sa'ib bin Malik السائب بن مالك; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
should I not tell you about me and about Fatimah, daughter of the Messenger of Allah (May peace be upon him). She was dearest to him of his family. When she was with me, she pulled mill-stone which affected her hand; she carried water with the water-bag which affected the upper portion of her chest: She swept the house so much so that her clothes became dusty; and she cooked food by which her clothes became black, and it harmed her. We heard that some slaves had been brought to the prophet (May
Grade: Da'if

Hadith #5139 - Sunan Abi Dawud - Aabad bin Musa al-Khtly عباد بن موسى الختلي; Abdullah bin 'Amr bin al-'Aas; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن (Sunan Abi Dawud)
I said: Messenger of Allah! to whom should I show kindness? He replied: Your mother, next your mother, next your mother, and then comes your father, and then your relatives in order of relationship. The Messenger of Allah (ﷺ) said: If a man asks his slave whom he freed for giving him property which is surplus with him and he refuses to give it to him, the surplus property which he refused to give will be called on the Day of resurrection as a large bald snake. Abu Dawud said: Aqra’ means a s
Grade: Hasan Sahih

Hadith #5150 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Mujahid bin Jabir مجاهد بن جبر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Sahl (b. Sa’d) reported the prophet (May peace be upon him) as saying; I and the one who takes the responsibility of an orphan will be in Paradise thus, and he joined his middle finger and forefinger.
Grade: Sahih

Hadith #5162 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Hameed bin Han'i Abu حميد بن هانئ أبو هانئ (Sunan Abi Dawud)
The Prophet (ﷺ) said: Treating those under one’s authority will produce prosperity, but an evil nature produces evil fortune.
Grade: Da'if

Hadith #5192 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; al-Laith bin Sa'd الليث بن سعد; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
Ikrimah said: A group of people from Iraq said: Ibn Abbas, what is your opinion about the verse in which we have been commanded whatever we have been commanded, but no one acts upon it? The word of Allah, Most High, reads: “O ye who believe! Let those whom your right hands possess, and the (children) among you, who have not come of age, ask your permission (before) they enter your presence on three occasions: before morning prayer, while you are undressing for the noonday heat, and after late-
Grade: Hasan

Hadith #5233 - Sunan Abi Dawud - Abdullah bin 'Amr bin al-'Aas; Hafs bin Ghyath حفص بن غياث; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
I was present with the Messenger of Allah at the battle of Hunayn. We travelled on a hot day when the heat was extreme. We halted under the shade of a tree. When the sun passed the meridian, I put on my coat of mail and rode on my horse. I came to the Messenger of Allah (ﷺ) who was in a tent. I said: Peace, Allah’s mercy and His blessings be upon you! The time of departure has come. He said: Yes. He then said: Rise, Bilal. He jumped out from beneath a gum-acacia tree and its shade was like t
Grade: Hasan